Electrochemical sensors based on molecularly imprinted polymer on nanostructured carbon materials: A review - Beluomini, Maísa Azevedo [UNESP]; da Silva, José Luiz [UNESP]; de Sá, Acelino Cardoso [UNESP]; Buffon, Edervaldo [UNESP]; Pereira, Thulio César [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2019)
This review provides a comprehensive overview of recent research on electrochemical sensors based on molecularly imprinted polymers (MIPs) on nanostructured carbon material surfaces for electrochemical detection. The combination of polymers and carbon nanomaterials for the development of electrochemical sensors unfolds new research opportunities in this area by virtue of the underlying properties of this class of sensors which include biocompatibility and excellent sensitivity, selectivity and stability. Furthermore, the aim of this review is to highlight recent achievements in analytical applications of these MIP-based electrochemical sensors in nanostructured carbon material for a wide range of sensing technologies.
Keywords: Carbon nanotubes; Electrochemical sensor; Fullerenes; Graphene; Molecularly imprinted polymer